Pengembangan dan Penerapan Aplikasi Mobile-Desktop Hybrid untuk Efisiensi Pencatatan Koleksi Buku pada UD Ndarik Helm Collection - Yunianita Rahmawati (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
UD Ndarik Helm Collection faced challenges in manually managing its book collection, particularly in recording data that required uploading cover photos and writing synopses, which slowed down the data entry process. This community service aimed to develop and implement a Mobile-Desktop Hybrid Application to facilitate book collection recording via mobile devices and provide integration with a desktop application for management and reporting. The abdimas method consisted of three stages: (1) Preparation – analyzing the old system to formulate the requirements for the new application, (2) Implementation – implementing the mobile and desktop hybrid application and conducting system testing, and (3) Evaluation – assisting users in operating the application and monitoring its effectiveness through user feedback. The application testing using the Likert scale showed a high level of satisfaction, with 92% of respondents rating the application as easy to use and efficient in managing the collection.